Time-to-first-event versus recurrent-event analysis: points to consider for selecting a meaningful analysis strategy in clinical trials with composite endpoints - Rauch, Geraldine; Kieser, Meinhard (Clinical research in cardiology, 2018)
Background Composite endpoints combining several event types of clinical interest often define the primary efficacy outcome in cardiologic trials. They are commonly evaluated as time-to-first-event,...
Published online: 16 February 2018
Gesehen am 08.05.2019